Comparison between ductility examination and a new approach based on strain hardening analysis to support the determination of proper austempering times. (2nd January 2020) - Angella, Giuliano; Ripamonti, Dario; Górny, Marcin
ABSTRACT: Austempered Ductile Irons (ADIs) with different contents of nickel and copper were austenitized at the same conditions, and austempered for 60, 90 and 180 min to investigate the austempering evolution. Besides the conventional ductility analysis to assess the best austempering times, strain hardening analysis of tensile flow curves was carried out, since it has been found reliable for this assessment if dislocation-density-related constitutive equations are used. Through plotting the Voce equation parameters 1/εc  vs. ϴo  found from the strain hardening analysis, Matrix Assessment Diagrams (MADs) were drawn, and austempering conditions closest to the best austempering times were identified. Austempering times found with ductility-criterion and MAD approach did not match. Mg–Cu particles found in copper-containing ADIs affected the reliability of tensile ductility that could not be ascribed to ausferrite stability only, while the austempering times found with MAD approach seemed to be consistent with solid-state diffusion transformations.